"The worth of a wildflower" Precautionary perspectives on the environmental risk of GMOs - Iulie Aslaksen; Anne Ingeborg Myhr (Statistics Norway, Research Department, 2006)
How much is a wildflower worth? Inspired by "The worth of a songbird" by Funtowicz and Ravetz (1994) we use the value of a wildflower as symbol of the complexity of evaluating environmental qualities and risks. We critically discuss the application of cost-benefit analysis in evaluating environmental impacts of adoption of genetically modified organisms (GMOs). We argue that cost-benefit analysis should be supplemented with other methods, such as processes for assessing uncertainty, accommodation of scientific disagreements, and integration of stakeholders' interests and perspectives. A more inclusive perspective is to develop precautionary approaches that recognize the multidimensional nature of environmental qualities and risks, such as irreplaceability, irreversibility, uncertainty and complexity. Precautionary approaches can contribute to develop a stronger environmental responsibility within the framework of rational self-interest.
Keywords: D81; Q20; Q50; 330; cost-benefit analysis; environmental risk; environmental value; genetically modified organisms; precautionary principle; scientific uncertainty